Nutritional and physical characteristics of noodles incorporated with green seaweed (Ulva reticulata) and fish (Pangasianodon hypophthalmus) mince - Debbarma, Jesmi; Viji, P.; Rao, B. M.; Prasad, M. M. (Indian Journal of Fisheries, 2017)
Nutritional and physical properties of noodles incorporated with green seaweed (Ulva reticulata) puree and fish (Pangasionodon hypophthalmus) mince were evaluated. Four lots of noodles were prepared using different formulations viz., control noodle without adding seaweed puree or fish meat (C); noodle with 20% cooked pangasius fish meat (T1), noodles with 20% seaweed puree (T2) and noodles with 10% seaweed puree and 10% cooked pangasius fish meat (T3). Proximate composition, cooking properties, textural and sensory qualities of noodles were assessed. Results indicated that addition of green seaweed puree increased the crude fibre content of noodles. Crude fibre content was higher in T2 (2.62±0.18%) followed by T3 (1.71±0.06%). Cooking time for noodles varied between 6.80±0.71 and 9.15±0.21 min and cooking loss was significantly (p